The effectiveness of peer group health education in improving adolescents’ knowledge of menstrual personal hygiene - Masytah, Masytah; Fitriani, Henny; Utami, Rahayu Budi (ELECTRON (Journal of Science and Technology), 2024)
Adolescents often lack adequate knowledge about personal hygiene during menstruation, which can increase the risk of reproductive health problems. Effective educational strategies, such as the peer group method, are needed to improve adolescents’ understanding because information delivered by peers tends to be more easily accepted and understood. This study aimed to determine the differences in adolescents’ knowledge before and after receiving health education using the peer group method on personal hygiene during menstruation at SMP Negeri 21 Pontianak. This research employed a quasi-experimental one-group pretest–posttest design involving 34 respondents selected through probability sampling. Data were collected from March 26 to April 3, 2019, using a structured questionnaire. Univariate and bivariate analyses were conducted to examine changes in knowledge levels. The results showed a p-value of 0.001, indicating a statistically significant difference in knowledge before and after the intervention (p < 0.05). The findings demonstrate that peer group–based health education is effective in increasing adolescents’ knowledge regarding menstrual personal hygiene. Therefore, the peer group method can be considered a beneficial approach for reproductive health education among young women at SMP Negeri 21 Pontianak.